Direct effects of colchicine on myocardial function: studies in hypertrophied and failing spontaneously hypertensive rats - Cicogna, A. C. [UNESP]; Robinson, K. G.; Conrad, C. H.; Singh, K.; Squire, R.; Okoshi, M. P.; Bing, O. H. (Hypertension, 1999)
The aging spontaneously hypertensive rat (SHR) is a model in which the transition from chronic stable left ventricular hypertrophy to overt heart failure can be observed. Although the mechanisms for impaired function in hypertrophied and failing cardiac muscle from the SHR have been studied, none accounts fully for the myocardial contractile abnormalities. The cardiac cytoskeleton has been implicated as a possible cause for myocardial dysfunction. If an increase in microtubules contributes to dysfunction, then myocardial microtubule disruption by colchicine should promote an improvement in cardiac performance. We studied the active and passive properties of isolated left ventricular papillary muscles from 18- to 24-month-old SHR with evidence of heart failure (SHR-F, n=6), age-matched SHR without heart failure (SHR-NF, n=6), and age-matched normotensive Wistar-Kyoto rats (WKY, n=5). Mechanical parameters were analyzed before and up to 90 minutes after the addition of colchicine (10(-5), 10(-4), and 10(-3) mol/L). In the baseline state, active tension (AT) developed by papillary muscles from the WKY group was greater than for SHR-NF and SHR-F groups (WKY 5.69+/-1.47 g/mm2 [mean+/-SD], SHR-NF 3.41+/-1.05, SHR-F 2.87+/-0.26; SHR-NF and SHR-F P<0.05 versus WKY rats). The passive stiffness was greater in SHR-F than in the WKY and SHR-NF groups (central segment exponential stiffness constant, Kcs: SHR-F 70+/-25, SHR-NF 44+/-17, WKY 41+/-13 [mean+/-SD]; SHR-F P<0.05 versus SHR-NF and WKY rats). AT did not improve after 10, 20, and 30 minutes of exposure to colchicine (10(-5), 10(-4), and 10(-3) mol/L) in any group. In the SHR-F group, AT and passive stiffness did not change after 30 to 90 minutes of colchicine exposure (10(-4) mol/L). In summary, the data in this study fail to demonstrate improvement of intrinsic muscle function in SHR with heart failure after colchicine. Thus, in the SHR there is no evidence that colchicine-induced cardiac microtubular depolymerization affects the active or passive properties of hypertrophied or failing left ventricular myocardium.